“M-Home Automation”: smart home application - Soosay Nathan, Shelena; Azman, Muhammad Hazim; Mohd Nor, Niza Afiqah; Mohd Zeki, Nur Afiqah Syazwani (Penerbit UTHM, 2020)
Smart home application is not a new thing for people nowadays. Smart Home concept have been applied everywhere these days. It is a technology in which user or homeowner can control their house using their own smartphones from far if they are not home. Smart Home is one of the brilliant creations of Internet of Things (IoT) and it shows how it helped the user a lot. The purpose of this paper is to present the evaluation and the implementation of M-HOME Automation that can integrate with a house using IoT. M-HOME Automation has its own ability to control the light, the fan and the gate of a house. Smartphone is used as the platform that will send any commands needed by user by clicking any function buttons and it has to be connected to the Bluetooth module, which is already plugged on the Arduino board. The development of the project is undertaken by following analysis design concept, which is ADDIE model. The last three phases, which are development, implementation and evaluation, is the most important phases to find this project as successful. A lot of improvements and corrections were made to make this project useful and efficient by the concept of Internet of Things. The prototype will ensure the users experiencing Smart Home with M-HOME Automation.